The Influence of Personal Branding, Influencer Endorsement, and Customer Engagement on Brand Affinity in the Cosmetics Industry in Indonesia - Frans Sudirjo; Darmiono Darmiono; Muhamad Ammar Muhtadi (Westscience Press, 2024)
This quantitative study explores the influence of personal branding, influencer endorsement, and customer engagement on brand affinity within the cosmetics industry in Indonesia. A sample of 176 cosmetic consumers was surveyed, and data were analyzed using structural equation modeling (SEM) with partial least squares (PLS) path analysis. The findings reveal significant positive relationships between personal branding, influencer endorsement, customer engagement, and brand affinity. Specifically, personal branding and influencer endorsement were found to have strong positive effects on brand affinity, highlighting the importance of cultivating a distinct brand identity and leveraging influencer partnerships to resonate with consumers. Additionally, customer engagement emerged as a critical determinant of brand affinity, underscoring the value of fostering meaningful interactions and experiences with consumers. These findings provide valuable insights for cosmetic brands seeking to enhance consumer perceptions and behaviors, drive brand loyalty, and achieve long-term success in the Indonesian market.